Canção moderna de província: repensando o Clube da Esquina e a história da música popular brasileira - Gabriel Reis Martins (2022)
This work proposes a reading of the work of Clube da Esquina – a musical group of Belo Horizonte – from a historical-literary perspective that makes use of the idea of “modernismo de província” (a provincial inflection of Brazilian Modernism), suggesting an approximation between Minas Gerais' musical trajectory in the decades of the 1960s and 1970s and the literary movements made in the 1920s and 1930s. With this aim, we chose as theoretical and critical references the works written by Gilles Deleuze and Félix Guattari, Ivan Marques and Santuza Cambraia Naves. At first, we discussed the methods and perspectives of the historiography of Brazilian Popular Music (MPB), in order to identify its relations with the history of literature, particularly with regard to the status it attributes to Modernism and to the “Semana de Arte Moderna”. After this, we make a reading of MPB that is guided by the eccentric position of Minas Gerais' Modernism in relation to that of São Paulo, in order to interpret the place of Clube da Esquina in musical history as that of a “canção moderna de província” (a modern provincial music). Besides, we also added interpretations based on post-structuralist theories of a Minor Literature. Finally, we analyze the records Milton (1970) and Lô Borges (1972) from a perspective that aims to identify points of destabilization of a traditional and evolutionary perspective of Brazilian musical history